Numerical analysis of an annular water–air jet pump with self-induced oscillation mixing chamber. (March 2017) - Deng, Xiaogang; Dong, Jingliang; Wang, Zhentao; Tu, Jiyuan
This paper presents an improved annular water–air jet pump concept design through integrating a self-induced oscillation mixing chamber with the conventional annular jet pump (AJP). The internal flow characteristics for both conventional and improved AJP were numerically investigated and compared by a validated computational fluid dynamics model. The numerical comparison demonstrated an approximately 10% pumping performance increase compared with the conventional pump, which is mostly attributed to the improved mass and energy transfer along the oscillating phase interface. Furthermore, transient flow analysis was conducted to resolve the unsteady self-introduced oscillation. The results revealed the self-introduced oscillation induces a continuous break-up and formation of fresh water–air interfaces, which exhibits a periodic feature with a dominant frequency of 147 Hz for the current design under given operational conditions. This study contributes toward a better understanding of the internal annular water–air jet pump flow patterns, and also demonstrates the feasibility of incorporating self-introduced oscillation chamber into AJP design.